Assessment of Egyptian Mothers' Knowledge and Domestic Management Practices of Fever in Preschool Children in Zagazig City, Sharkia Governorate - Eman H. Waly; Huny M. Bakry (MDPI AG, 2022)
(1) Background: Childhood fever is a frequent reason for health care visits. Parents are worried about fever and its complications and show variation between their knowledge about managing fever and real practice, which are affected by many factors and beliefs. This study aimed to assess knowledge of Egyptian mothers about fever of preschool children and its domestic management and the relation between them and to identify sociodemographic factors affecting mothers' knowledge and practice. (2) Methods: a cross-sectional study was conducted at the pediatric outpatient clinic at Zagazig University Hospitals among 297 mothers with preschool children. A structured questionnaire consisting of three parts assessed the sociodemographic characteristics, mothers' knowledge about childhood fever, and its management practices. (3) Results: 37.7% of mothers had good knowledge about childhood fever, and 23.9% showed good management practices. Young mothers, less number of children, high education, sufficient income, and good knowledge were the significant predictors of domestic management practices towards childhood fever. (4) Conclusions: The Egyptian mothers showed insufficient levels of knowledge and domestic management practices towards preschool childhood fever. Health education interventions should be targeted to mothers to improve their knowledge and practice.